Wild beauty - McLemore, Anna-Marie (Feiwel and Friends, 2017)
For nearly a century, the Nomeolvides women have tended the grounds of La Pradera, hiding a terrible legacy, until mysterious Fel arrives and Estrella helps him explore his dangerous past